Total laparoscopic hysterectomy of an endocervical pyomyoma over previous cesarean section wound - Phornsawan Wasinghon; Kuan- Gen Huang; Siew- Yen Lai (Wolters Kluwer Medknow Publications, 2020)
A 41-year-old female, G2P2, who experienced menorrhagia for 1 month, had had a history of myoma uteri for the previous 5 years. The computed tomography showed a leiomyoma mass of approximately 8 cm. She underwent a total laparoscopic hysterectomy with bilateral salpingectomy. This pyomyoma originated in the endocervix over the cesarean section wound. The postoperative care was uneventful. Pyomyoma is a rare condition and is even rarer in premenopausal patients without a history of pregnancy or uterine instrumentation. The spontaneous pyomyoma at the endocervical leiomyoma demonstrated an unusual case in the absence of risk factors. Pyomyoma could be considered as a diagnosis in patients without fever, history of fibroids, and no other identifiable sources of infection.